Prebisch and Singer in the Egyptian cotton fields - Diab, Osama (My University, 2023)
By emphasising the role of historical contingency in determining the losers and winners of economic interaction, the article argues that barter terms of trade (BTT) evolution is key to understanding central phenomena of the modern capitalist era apart from Weberian and Sombartian culturalist interpretations. By examining BTT data between Egypt and Britain in the long 19th century, the article demonstrates how it was a rational choice by an independent economy to commit to a 'peripheral' comparative advantage as future value evolution could not have been predicted at the onset of such commitment. Relying on previously unpublished archival records, the article also explores the role of empire and political power in determining supply and demand and hence value evolution, challenging neoclassical assumptions about the central role of consumer choice in influencing supply, demand and commodity value. The article argues that the BTT evolution is key to understanding two central phenomena of the modern capitalist era away from Weberian- and Sombartian-style culturalist interpretations. First is the growing uneven development–known as the Great Divergence–between the 'core' and the 'periphery' of the global economic system, and second is the rise of anti-colonial sentiments and policies in the Global South.
Keywords: Egypt; Cotton fields